Morphodynamics of Hue tidal inlets, Vietnam / :Asian and Pacific Coasts 2007 September 21-24, 2007, Nanjing, China. - Verhagen, Henk Jan (China, 2020)
Morphodynamics of a tidal inlet system on a micro-tidal coast in a tropical monsoon influenced region is modelled and discussed . Effects of tides, waves, river flows and system configuration on the inlet morphologies are investigated with the aid of process-based state-of-the-art numerical models. Seasonal and episodic behaviour of the inlet system under the influence of the forcing processes is th en described, modelled and explained.